Humane Euthanasia of Sick, Injured, and/or Debilitated Livestock - Jan K. Shearer; Paul Nicoletti (EDIS, 2007)
Revised! VM-152, a 16-page full-color publication by Jan K. Shearer and Paul Nicoletti, includes sections on indications for euthanasia, methods, anatomical landmarks, exsanguination, and confirmation of death. Includes references. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, January 2002. Revised April 2007.